Method for liquid-phase regeneration of lithium iron phosphate positive electrode material, positive electrode plate and battery
The liquid phase regeneration method is used to pretreat, strip and replenish lithium for waste lithium iron phosphate cathode materials, which solves the problem of lithium vacancy defects and structural damage caused by high temperature treatment, achieves rapid repair and electrochemical improvement of materials, and improves recycling efficiency and economic benefits.
Patent Information
- Application Number
- CN202411772873.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, when dealing with waste lithium iron phosphate batteries, there are problems such as lithium vacancy defects and lithium sites occupying the space of iron, resulting in iron oxidation and structural reaction defects, thereby blocking the diffusion path of Li2+, and high-temperature treatment leads to material structure damage. and environmental pollution.
The liquid -phase regeneration method is used to prepare, peel off, and supplement lithium lithium iconic material for the iconic pole material of waste phosphates. The lithium+uniformly distributed and freely spread through a mild liquid -phase environment, and the supplementary effect of lithium deficiency is improved.
The rapid repair and electrochemical improvement of lithium iron phosphate materials are realized, and the material structure damage and environmental pollution caused by high temperature treatment are avoided, and the recovery rate and economic benefits of materials are improved.
Smart Images

Figure CN119361888A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, and in particular to a method for liquid-phase regeneration of lithium iron phosphate positive electrode materials, a positive electrode sheet and a battery. Background Art
[0002] As an important member of modern energy storage, lithium iron phosphate batteries have outstanding performance in new energy vehicles, large energy storage systems and portable electronic devices. Usually, the number of cycles of lithium iron phosphate batteries is generally between 500 and 2000 times. After reaching a service life of 3 to 5 years, they will be retired. The main reason for battery retirement is that lithium iron phosphate battery positive electrode materials have lithium vacancy defects during charging and discharging, and lithium sites are occupied by iron, resulting in iron oxidation, while inducing some Fe in its own structure to 2+ Migrate to the lithium site, forming a reaction defect, thereby blocking the Li 2+ diffusion pathway.
[0003] In some related technologies, retired lithium iron phosphate batteries are directly landfilled or disposed of inappropriately, and the toxic organic matter, organic electrolyte and metal ions contained in them will gradually seep into the soil and groundwater, causing environmental pollution and waste of resources. At present, waste lithium iron phosphate is usually regenerated by solid phase sintering, electrochemical method and hydrothermal method, which requires high reaction temperature and there is non-uniform reaction in the lithium replenishment process, which has poor effect on replenishing lithium-deficient sites. Summary of the invention
[0004] In order to solve at least one of the problems mentioned in the above background technology, the present application provides a method for liquid phase regeneration of lithium iron phosphate positive electrode material, a positive electrode plate and a battery, which can achieve lithium replenishment in a relatively mild liquid phase environment, and make the soluble Li + Evenly distributed, freely diffuse and move in the solution, so that Li + It contacts the supplementation site more fully, thus improving the supplementation effect of the lithium-deficient site.
[0005] The specific technical solutions provided by the embodiments of this application are as follows:
[0006] In a first aspect, a method for liquid phase regeneration of lithium iron phosphate positive electrode material is provided, the method comprising:
[0007] Pre-treating waste lithium iron phosphate materials to obtain pre-treated lithium iron phosphate positive electrode sheets;
[0008] Immersing the pretreated lithium iron phosphate positive electrode sheet in a deionized liquid to obtain stripped lithium iron phosphate;
[0009] A lithium replenishing solution is prepared, and the stripped lithium iron phosphate is immersed in the lithium replenishing solution, and reacted for a first preset time under an inert atmosphere to obtain a reacted mixture;
[0010] The solid in the reaction mixture is separated and dried to obtain the regenerated lithium iron phosphate material.
[0011] In a specific embodiment, the pretreated lithium iron phosphate positive electrode sheet is immersed in deionized liquid to obtain stripped lithium iron phosphate, which specifically includes: immersing the pretreated lithium iron phosphate positive electrode sheet in deionized water and maintaining it for a second preset time to obtain separated lithium iron phosphate; placing the separated lithium iron phosphate in a blast oven and a vacuum oven in turn for drying to obtain the stripped lithium iron phosphate.
[0012] In a specific embodiment, the method further includes: the temperature of the deionized water is set to 60-100° C.; the second preset time is 3-5 minutes; the drying time in the blast oven is 24-48 hours; and the drying time in the vacuum oven is 24-48 hours.
[0013] In a specific embodiment, the stripped lithium iron phosphate is in the form of flakes or particles, and the surface area of the stripped lithium iron phosphate is in the range of 1.5 to 4 mm 2 ; The particle size of the granular exfoliated lithium iron phosphate is 20 to 100 mesh.
[0014] In a specific embodiment, a lithium salt, a reducing substance and a polar solvent are mixed in a preset ratio to form a mixed solution, and the pH value of the mixed solution is adjusted to a preset pH value to obtain the lithium replenishing solution; the stripped lithium iron phosphate is immersed in the lithium replenishing solution, kept in a sealed state, and set in the inert atmosphere, and heated and stirred to react for the first preset time.
[0015] In a specific embodiment, the preset pH value is 8 to 12; the heating temperature is 40 to 100° C., the stirring speed is 500 to 1500 rpm; and the first preset time is 2 to 6 hours.
[0016] In a specific embodiment, the lithium salt includes at least one or more of lithium chloride, lithium iodide, lithium phosphate, lithium carbonate, lithium hydroxide, lithium bromide, lithium nitrate, lithium sulfate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium acetate, lithium bis(oxalatoborate), lithium tetrafluoroborate or lithium acrylate;
[0017] The reducing substance includes at least one or more of lithium aluminum hydride, sodium thiocyanate, sodium sulfide, ascorbic acid, citric acid, glucose, fructose, lactose, maltose, potassium tris(1-pyrazolyl)borohydride, sodium triacetoxyborohydride, sodium sulfite, ferrous chloride tetrahydrate or stannous chloride;
[0018] The polar solvent includes at least one or more of ethanol, methanol, acetone, ethyl acetate, dimethyl sulfoxide, glycerol, acetonitrile, tetrahydrofuran, acetic acid, N,N-dimethylamide, pyridine, dimethylacetamide, dioxane, N-methylpyrrolidone or hexamethylammonium phosphate;
[0019] The inert atmosphere includes at least one or more of nitrogen, argon or helium.
[0020] In a specific embodiment, the method further includes: using a centrifugal device to separate the solids in the reaction mixture, wherein the rotation speed of the centrifugal device is 8000-15000 r / min; using a blast oven and a vacuum oven to dry the solids in sequence; wherein the temperature of the blast oven to dry the solids is 80-100°C, and the drying time is 8-12 hours; wherein the temperature of the vacuum oven to dry the solids is 120-150°C, and the drying time is 24-48 hours.
[0021] In a second aspect, a positive electrode plate is provided, wherein the positive electrode plate is prepared by the method for liquid phase regeneration of lithium iron phosphate positive electrode material as described above.
[0022] In a third aspect, a battery is provided, wherein the battery comprises the positive electrode plate as described above or the positive electrode plate in the battery is prepared by the method for liquid phase regeneration of lithium iron phosphate positive electrode material as described above.
[0023] The embodiments of the present application have the following beneficial effects:
[0024] 1. The solution provided in the embodiment of the present application is to pretreat the waste lithium iron phosphate to obtain a pretreated lithium iron phosphate positive electrode sheet, and immerse the lithium iron phosphate positive electrode sheet in a mild liquid phase to obtain stripped lithium iron phosphate, and then place the fragments in a lithium replenishing solution, and carry out a lithium replenishing reaction under an inert atmosphere, so that the freely moving lithium ions can quickly find and fill the lithium vacancies in the positive electrode material, so that the lithium ions can more fully contact the replenishment sites, thereby improving the replenishment effect of the lithium-deficient sites, thereby achieving rapid repair and electrochemical improvement of the waste lithium iron phosphate material.
[0025] 2. This scheme adopts a more gentle liquid phase repair operation, which effectively avoids the structural damage of the material caused by the high-temperature treatment process compared to the solid phase sintering method. The gentle operation not only reduces losses, but also reduces the requirements for equipment, and improves the safety and feasibility of the operation. At the same time, the liquid phase lithium replenishment process avoids the harmful gases and pollutants that may be produced during the high-temperature calcination process, reducing the risk of secondary pollution. At the same time, the precise control of reaction conditions and the selection of chemical additives optimize the performance of the regenerated lithium iron phosphate material, and improve the recycling rate and economic benefits of the lithium iron phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 A schematic diagram of a method for liquid phase regeneration of lithium iron phosphate positive electrode material according to Example 1 of the present application is shown;
[0028] Figure 2 A schematic diagram of a recovery rate test for stripping lithium iron phosphate according to the present application is shown;
[0029] Figure 3 The XRD test results of the regenerated lithium iron phosphate material before and after lithium supplementation according to the present application are shown;
[0030] Figure 4 The results of rate test and charge-discharge curve test of the regenerated lithium iron phosphate material before and after lithium supplementation according to the present application are shown;
[0031] Figure 5 The figure shows the cycle test results of the regenerated lithium iron phosphate material in the capacitor according to the present application. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0034] Embodiment 1
[0035] A method for liquid phase regeneration of lithium iron phosphate positive electrode material is provided, such as Figure 1 As shown, the method comprises the following steps:
[0036] Step S1, pre-treating waste lithium iron phosphate materials to obtain pre-treated lithium iron phosphate positive electrode sheets.
[0037] Specifically, it includes electrochemical discharge and disassembly pre-treatment of waste lithium iron phosphate materials to consume the electric charge in the waste lithium iron phosphate materials to improve the safety of the regeneration process of the lithium iron phosphate materials.
[0038] Step S2: immersing the pretreated lithium iron phosphate positive electrode sheet in a deionized liquid to obtain stripped lithium iron phosphate.
[0039] It should be noted that the deionized liquid in this embodiment is selected as deionized water, which specifically includes: immersing the pretreated lithium iron phosphate positive electrode sheet in deionized water and maintaining it for a second preset time to obtain separated lithium iron phosphate; placing the separated lithium iron phosphate in a blast oven and a vacuum oven in turn for drying to obtain the stripped lithium iron phosphate.
[0040] The temperature of the deionized water is set to 60-100° C.; the second preset time is 3-5 minutes; the drying time in the blast oven is 24-48 hours; and the drying time in the vacuum oven is 24-48 hours.
[0041] In order to enhance the reaction effect of the stripped lithium iron phosphate in the subsequent processing process, the stripped lithium iron phosphate is selected to be in the form of flakes or particles, and the surface area of the flake-shaped stripped lithium iron phosphate ranges from 1.5 to 4 mm 2 ; The particle size of the granular exfoliated lithium iron phosphate is 20 to 100 mesh.
[0042] Step S3, preparing a lithium replenishing solution, and immersing the stripped lithium iron phosphate in the lithium replenishing solution, and reacting for a first preset time under an inert atmosphere to obtain a reacted mixture.
[0043] In a specific embodiment, the steps include mixing a lithium salt, a reducing substance, and a polar solvent in a preset ratio to form a mixed solution, and adjusting the pH value of the mixed solution to a preset pH value to obtain the lithium replenishing solution; immersing the stripped lithium iron phosphate in the lithium replenishing solution, maintaining a sealed state, and setting the inert atmosphere to heat and stir the reaction for the first preset time.
[0044] Among them, the molar mass ratio of lithium salt to reducing substance in the lithium replenishing solution is 3 to 1:2, the mixed solution also includes deionized water, the volume ratio of deionized water to polar solvent is 10 to 8:1, and the above substances are mixed according to the above ratio to form a mixed solution; the preset pH value of the mixed solution is 8 to 12; the heating temperature is 40 to 100°C, and the stirring speed is 500 to 1500rpm; the first preset time is 2 to 6h.
[0045] In a specific embodiment, the lithium salt includes but is not limited to one or more of lithium chloride, lithium iodide, lithium phosphate, lithium carbonate, lithium hydroxide, lithium bromide, lithium nitrate, lithium sulfate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium acetate, lithium bis(oxalatoborate), lithium tetrafluoroborate or lithium acrylate;
[0046] The reducing substance includes, but is not limited to, one or more of lithium aluminum hydride, sodium thiocyanate, sodium sulfide, ascorbic acid, citric acid, glucose, fructose, lactose, maltose, potassium tris(1-pyrazolyl)borohydride, sodium triacetoxyborohydride, sodium sulfite, ferrous chloride tetrahydrate or stannous chloride;
[0047] The polar solvent includes, but is not limited to, one or more of ethanol, methanol, acetone, ethyl acetate, dimethyl sulfoxide, glycerol, acetonitrile, tetrahydrofuran, acetic acid, N,N-dimethylamide, pyridine, dimethylacetamide, dioxane, N-methylpyrrolidone or hexamethylammonium phosphate;
[0048] The inert atmosphere includes, but is not limited to, one or more of nitrogen, argon or helium.
[0049] Step S4, separating the solid in the reaction mixture, and drying the solid to obtain regenerated lithium iron phosphate material.
[0050] A centrifugal device is used to separate the solid in the reaction mixture, wherein the rotation speed of the centrifugal device is 8000-15000 r / min; deionized water is used for washing during centrifugation, and then a blast oven and a vacuum oven are used to dry the solid in sequence; wherein the temperature of the blast oven drying the solid is 80-100°C, and the drying time is 8-12 hours; wherein the temperature of the vacuum oven drying the solid is 120-150°C, and the drying time is 24-48 hours, and a gray powder can be obtained, and the gray powder is the regenerated lithium iron phosphate material.
[0051] Embodiment 2
[0052] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 60°C deionized water for 5 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0053] 0.6 mol lithium carbonate and 0.4 mol ascorbic acid were dissolved in deionized water and N'N-dimethylamide in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 8; the stripped lithium iron phosphate obtained above was ground, and 100 g of the stripped lithium iron phosphate with a mesh size of 100 was immersed in a sealed device filled with the lithium supplement solution, and argon gas was passed as a protective gas; the stirring speed was set to 1500 rpm, and the reaction was carried out at 100° C. for 6 hours;
[0054] The reaction mixture was centrifuged at 15000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h. It was then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0055] Embodiment 3
[0056] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 100°C deionized water for 3 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; and the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0057] 0.6 mol lithium carbonate and 0.4 mol citric acid were dissolved in deionized water and dimethyl sulfoxide in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 8; the stripped lithium iron phosphate obtained above was ground and 100 g, 4 mm 2 The stripped lithium iron phosphate was immersed in a sealed device filled with the above lithium supplement solution, and argon gas was introduced as a protective gas; the stirring speed was set to 1500 rpm, and the reaction was carried out at 100° C. for 6 hours;
[0058] The reaction mixture was centrifuged at 15000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h. It was then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0059] Embodiment 4
[0060] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 80°C deionized water for 5 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0061] 0.6 mol lithium phosphate and 0.4 mol sodium sulfite were dissolved in deionized water and pyridine in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 8; the stripped lithium iron phosphate obtained above was ground, and 100 g of the stripped lithium iron phosphate with a mesh size of 20 was immersed in a sealed device containing the above lithium supplement solution, and argon gas was passed as a protective gas; the stirring speed was set to 500 rpm, and the reaction was carried out at 40° C. for 6 hours;
[0062] The reaction mixture was centrifuged at 8000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h, and then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0063] Embodiment 5
[0064] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 100°C deionized water for 3 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; and the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0065] 0.6 mol lithium phosphate and 0.4 mol sodium triacetoxyborohydride were dissolved in deionized water and N-methylpyrrolidone in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 8; the stripped lithium iron phosphate obtained above was ground, and 100 g of the stripped lithium iron phosphate with a mesh size of 100 was immersed in a sealed device filled with the above lithium supplement solution, and argon gas was passed as a protective gas; the stirring speed was set to 500 rpm, and the reaction was carried out at 80° C. for 6 hours;
[0066] The reaction mixture was centrifuged at 8000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h, and then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0067] Embodiment 6
[0068] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 100°C deionized water for 5 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0069] 0.6 mol lithium hydroxide and 0.4 mol ferrous chloride tetrahydrate were dissolved in deionized water and ethanol in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 10; the stripped lithium iron phosphate obtained above was ground and 100 g, 1.5 mm 2 The stripped lithium iron phosphate was immersed in a sealed device filled with the above lithium supplement solution, and nitrogen was passed as a protective gas; the stirring speed was set to 1500 rpm, and the reaction was carried out at 60° C. for 6 hours;
[0070] The reaction mixture was centrifuged at 15000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h. It was then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0071] Embodiment 7
[0072] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 100°C deionized water for 3 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; and the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0073] 0.6 mol lithium hydroxide and 0.4 mol potassium tri(1-pyrazolyl)borohydride were dissolved in deionized water and methanol in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 10; the stripped lithium iron phosphate obtained above was ground and 100 g, 1.5 mm 2 The stripped lithium iron phosphate was immersed in a sealed device filled with the above lithium supplement solution, and nitrogen was passed as a protective gas; the stirring speed was set to 1500 rpm, and the reaction was carried out at 80° C. for 6 hours;
[0074] The reaction mixture was centrifuged at 15000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h. It was then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0075] Embodiment 8
[0076] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 80°C deionized water for 4 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0077] 0.6 mol lithium bromide and 0.4 mol stannous chloride were dissolved in deionized water and glycerol in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 10; the stripped lithium iron phosphate obtained above was ground, and 100 g of the stripped lithium iron phosphate with a mesh size of 20 was immersed in a sealed device filled with the above lithium supplement solution, and nitrogen was introduced as a protective gas; the stirring speed was set to 500 rpm, and the reaction was carried out at 40° C. for 6 hours;
[0078] The reaction mixture was centrifuged at 8000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h, and then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0079] Embodiment 9
[0080] The waste lithium iron phosphate material is pretreated by electrochemical discharge and disassembly to obtain a pretreated lithium iron phosphate positive electrode sheet; the pretreated lithium iron phosphate positive electrode sheet is then immersed in 80°C deionized water for 3 minutes to separate the lithium iron phosphate and the current collector, thereby obtaining the stripped lithium iron phosphate; the pretreated lithium iron phosphate positive electrode sheet is transferred to a 100°C forced air oven for drying for 24 hours, and then transferred to a 120°C vacuum oven for drying for 48 hours, and the elemental composition and carbon content in the lithium iron phosphate material are weighed and determined;
[0081] 0.6 mol lithium bromide and 0.4 mol sodium sulfide were dissolved in deionized water and ethyl acetate in a volume ratio of 9:1, and the pH value of the lithium supplement solution was adjusted to 10; the stripped lithium iron phosphate obtained above was ground, and 100 g of the stripped lithium iron phosphate with a mesh size of 100 was immersed in a sealed device containing the above lithium supplement solution, and nitrogen was introduced as a protective gas; the stirring speed was set to 500 rpm, and the reaction was carried out at 60° C. for 6 hours;
[0082] The reaction mixture was centrifuged at 8000 rpm, washed three times with deionized water, and baked in a 100°C forced air oven for 12 h, and then transferred to a 150°C vacuum oven and baked for 48 h to obtain a gray powder, which is the regenerated lithium iron phosphate positive electrode material.
[0083] The preparation process of the liquid phase regenerated lithium iron phosphate positive electrode material in the above-mentioned embodiments 2 to 9 is obtained, and the recovery rate of the stripped lithium iron phosphate stripped in Embodiment 2, Embodiment 4, Embodiment 6 and Embodiment 8 is tested. The relevant test results are shown in Table 1, wherein the recovery rate of the stripped lithium iron phosphate stripped by deionized water in this embodiment is calculated using the following formula:
[0084]
[0085] Among them, M S Indicates the quality of stripped lithium iron phosphate; M P Indicates the quality of lithium iron phosphate positive electrode sheet pretreated by deionized water stripping; M Al represents the mass of the current collector aluminum foil stripped off by deionized water; R represents the recovery rate.
[0086] Table 1 Test results of each group of embodiments
[0087]
[0088]
[0089] Among them, Figure 2 As shown, combined with the recovery rate test data of the stripped lithium iron phosphate stripped in Example 2, Example 4, Example 6 and Example 8, it can be seen that by calculating the recovery rate of the stripped lithium iron phosphate stripped, it can be seen that by adopting the stripping conditions in this embodiment, the recovery rate of the stripped lithium iron phosphate stripped can be made above 80% at different temperatures; and the contents of lithium, iron, phosphorus and carbon in the regenerated lithium iron phosphate obtained by adopting the regeneration and lithium replenishment method in this embodiment are improved compared with the contents in the waste lithium iron phosphate before treatment, thereby proving the treatment effect of this scheme.
[0090] Furthermore, the regenerated lithium iron phosphate material prepared in Example 1 was subjected to XRD performance test before and after lithium supplementation. The test results are as follows: Figure 3 As shown, it can be seen that the regenerated lithium iron phosphate positive electrode material obtained by the treatment method in this embodiment does not add new impurity phases, and the obtained regenerated lithium iron phosphate positive electrode material conforms to the LiFePO4@C composite positive electrode material specified in JCPDS:77-0179.
[0091] The solution provided by the embodiment of the present application enables the freely moving lithium ions to quickly find and fill the lithium vacancies in the positive electrode material, so that the lithium ions can more fully contact the supplementary sites, improve the supplementary effect of the lithium-deficient sites, and thus achieve rapid repair and electrochemical improvement of waste lithium iron phosphate materials. And the use of a more gentle liquid phase repair operation effectively avoids the structural damage of the material caused by the high-temperature treatment process compared to the solid phase sintering method. The gentle operation not only reduces the loss, but also reduces the requirements for equipment, and improves the safety and feasibility of the operation; at the same time, the liquid phase lithium supplementation process avoids the harmful gases and pollutants that may be produced during the high-temperature calcination process, reducing the risk of secondary pollution. At the same time, the precise control of the reaction conditions and the selection of chemical additives optimize the performance of the regenerated lithium iron phosphate material, and improve the recycling rate and economic benefits of the lithium iron phosphate material.
[0092] Embodiment 10
[0093] Corresponding to the above embodiment, the present application provides a positive electrode plate, which is prepared by the method of liquid phase regeneration of lithium iron phosphate positive electrode material as described above.
[0094] Embodiment 11
[0095] Corresponding to the above embodiments, the present application provides a battery, which includes the positive electrode plate as described above, or the positive electrode plate in the battery is prepared by the method for liquid phase regeneration of lithium iron phosphate positive electrode material as described above.
[0096] In this embodiment, the regenerated lithium iron phosphate material prepared in Example 1 is used to assemble a lithium-ion battery, and the electrochemical performance test is carried out. The lithium-ion battery includes a positive electrode, a negative electrode and an electrolyte, and the lithium-ion battery includes but is not limited to a cylindrical battery, a square battery, a button battery and a sheet battery. The positive electrode, the negative electrode and the electrolyte of the lithium-ion battery are conventional structures in the art, wherein the positive electrode sheet includes a positive electrode material layer and a current collector, and the positive electrode material layer includes an active substance, a conductive agent and an adhesive, wherein the active substance is a regenerated lithium iron phosphate material, the conductive agent is conductive carbon black, and the adhesive is polyvinylidene fluoride, and the mass ratio of each is 8:1:1.
[0097] Furthermore, rate tests and charge-discharge performance tests were performed on the prepared regenerated lithium iron phosphate materials in the above-mentioned Examples 2 to 9 in capacitors, and the test results obtained are shown in Table 2.
[0098] Table 2 Rate test and charge-discharge performance test results of each group of examples
[0099]
[0100]
[0101] Combined with the test data in Table 2, it can be seen that the various battery performances of the regenerated lithium iron phosphate prepared by the method in this scheme are improved compared with the performance of the waste lithium iron phosphate material before treatment, which further verifies that the mild liquid phase repair operation adopted in this scheme enables the freely moving lithium ions to quickly find and fill the lithium vacancies in the positive electrode material, so that the lithium ions can more fully contact the replenishment sites, thereby improving the replenishment effect of the lithium-deficient sites; not only does it avoid the structural damage of the material caused by the high-temperature treatment process, but the mild operation can also reduce the loss, and also reduce the requirements for equipment, and improve the safety and feasibility of the operation.
[0102] Specifically, Figure 4 As shown, the rate test of retired lithium iron phosphate and the regenerated lithium iron phosphate material in the second embodiment in the supercapacitor ( Figure 4 a) and charge-discharge curves and ( Figure 4 b), it can be seen that the charge / discharge platform shows reversibility during the operation of the lithium-ion battery.
[0103] In a specific embodiment, Figure 5 As shown in the figure, the test results of the cycle test of the regenerated lithium iron phosphate material in the second embodiment in the supercapacitor are shown. Figure 5 It can be seen that the initial discharge capacity is 145.53 mAh g -1 After 250 cycles, the discharge capacity is 138.25 mAh g -1 , the capacity retention rate is as high as 95%, proving the stable electrochemical performance of the repaired and regenerated lithium iron phosphate.
[0104] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the embodiments of the present application.
[0105] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for liquid phase regeneration of lithium iron phosphate positive electrode material, characterized in that: The method comprises: Pre-treating waste lithium iron phosphate materials to obtain pre-treated lithium iron phosphate positive electrode sheets; Immersing the pretreated lithium iron phosphate positive electrode sheet in a deionized liquid to obtain stripped lithium iron phosphate; A lithium replenishing solution is prepared, and the stripped lithium iron phosphate is immersed in the lithium replenishing solution, and reacted for a first preset time under an inert atmosphere to obtain a reacted mixture; The solid in the reaction mixture is separated and dried to obtain the regenerated lithium iron phosphate material.
2. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to claim 1, characterized in that: The pretreated lithium iron phosphate positive electrode sheet is immersed in a deionized liquid to obtain the stripped lithium iron phosphate, specifically comprising: Immersing the pretreated lithium iron phosphate positive electrode sheet in deionized water and maintaining the water for a second preset time to obtain separated lithium iron phosphate; The separated lithium iron phosphate is placed in a blast oven and a vacuum oven in turn for drying to obtain the stripped lithium iron phosphate.
3. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to claim 2, characterized in that: The method further comprises: The temperature of the deionized water is set to 60-100° C.; the second preset time is 3-5 minutes; The drying time in the blast oven is 24 to 48 hours; the drying time in the vacuum oven is 24 to 48 hours.
4. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The stripped lithium iron phosphate is in the form of flakes or particles, and the surface area of the stripped lithium iron phosphate in the form of flakes is in the range of 1.5 to 4 mm 2 ; The particle size of the granular exfoliated lithium iron phosphate is 20 to 100 mesh.
5. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The method further comprises: Mixing a lithium salt, a reducing substance and a polar solvent in a preset ratio to form a mixed solution, and adjusting the pH value of the mixed solution to a preset pH value to obtain the lithium supplement solution; The stripped lithium iron phosphate is immersed in the lithium replenishing solution, kept in a sealed state, and set under the inert atmosphere, and heated and stirred to react for the first preset time.
6. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to claim 5, characterized in that: The method further comprises: The preset pH value is 8 to 12; The heating temperature is 40-100° C., the stirring speed is 500-1500 rpm; and the first preset time is 2-6 hours.
7. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to claim 5, characterized in that: The method further comprises: The lithium salt includes at least one or more of lithium chloride, lithium iodide, lithium phosphate, lithium carbonate, lithium hydroxide, lithium bromide, lithium nitrate, lithium sulfate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium acetate, lithium bis(oxalatoborate), lithium tetrafluoroborate or lithium acrylate; The reducing substance includes at least one or more of lithium aluminum hydride, sodium thiocyanate, sodium sulfide, ascorbic acid, citric acid, glucose, fructose, lactose, maltose, potassium tris(1-pyrazolyl)borohydride, sodium triacetoxyborohydride, sodium sulfite, ferrous chloride tetrahydrate or stannous chloride; The polar solvent includes at least one or more of ethanol, methanol, acetone, ethyl acetate, dimethyl sulfoxide, glycerol, acetonitrile, tetrahydrofuran, acetic acid, N,N-dimethylamide, pyridine, dimethylacetamide, dioxane, N-methylpyrrolidone or hexamethylammonium phosphate; The inert atmosphere includes at least one or more of nitrogen, argon or helium.
8. The method for liquid phase regeneration of lithium iron phosphate positive electrode material according to claim 5, characterized in that: The method further comprises: Using a centrifugal device to separate the solid in the reaction mixture, wherein the rotation speed of the centrifugal device is 8000-15000 r / min; Drying the solid in a forced air oven and then in a vacuum oven; The temperature of the blast oven for drying the solid is 80-100°C and the drying time is 8-12h; The temperature of the vacuum oven for drying the solid is 120-150° C., and the drying time is 24-48 hours.
9. A positive electrode sheet, characterized in that: The positive electrode plate is prepared by the method for liquid phase regeneration of lithium iron phosphate positive electrode material according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the positive electrode plate according to claim 9, or the positive electrode plate in the battery is prepared by the method for liquid phase regeneration of lithium iron phosphate positive electrode material according to any one of claims 1 to 8.
Citation Information
Cited By
Direct regeneration method of waste lithium iron phosphate positive electrode material based on hydroxylamine as reducing agent
CN120398021A